2021
DOI: 10.1111/desc.13199
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotion enhances conflict processing in preschoolers

Abstract: The rapid detection and resolution of conflict between opposing action tendencies is crucial for our ability to engage in goal-directed behavior. Research in adults suggests that emotions might serve as a 'relevance detector' that alarms attentional and sensory systems, thereby leading to more efficient conflict processing. In contrast, previous research in children has almost exclusively stressed the impeding influence of emotion on the attentional system, as suggested by the protracted development of perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In particular, Yanaoka et al (2022) reported that prior task experience influences engagement of proactive control at age 5, suggesting that young children may learn to use proactive control through the acquisition of abstract task knowledge that captures regularities of the task. Berger & Grosse Wiesmann (2022) reported a facilitation effect of positive emotion on conflict processing in 2-to 7-year-olds, hence suggesting that positive emotion can already trigger efficient control processes from early stages of self-regulation development.…”
mentioning
confidence: 95%
“…In particular, Yanaoka et al (2022) reported that prior task experience influences engagement of proactive control at age 5, suggesting that young children may learn to use proactive control through the acquisition of abstract task knowledge that captures regularities of the task. Berger & Grosse Wiesmann (2022) reported a facilitation effect of positive emotion on conflict processing in 2-to 7-year-olds, hence suggesting that positive emotion can already trigger efficient control processes from early stages of self-regulation development.…”
mentioning
confidence: 95%
“…With the continuous development of positive psychology, some scholars have paid attention to the important role of positive affect in work organizations. Studies (Berger & Grosse Wiesmann, 2022 ; Carmona‐Halty et al, 2021 ) have shown, people with high positive affect may choose higher goals, show greater determination to solve problems and be able to adopt more effective coping strategies. It can improve employees' job satisfaction, which in turn stimulates their work enthusiasm and creativity, and ultimately improves their job performance (Forjan et al, 2020 ; Kagwe et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%